Biological Properties of Dialysable Peptides Derived from Plasmin Digestion of Bovine Fibrinogen Preparations - Buczko, W; Gaetano, G. de; Franco, R; Donati, M. B (Thrombosis and Haemostasis, 1976)
Dialysable peptides (M. W. less than 12,000) were obtained by plasmin digests of purified bovine fibrinogen. The biological effects of these peptides were studied in rats in three different test systems: ADP-induced platelet aggregation, isolated atria contractility and vascular permeability.The effects induced by the peptides were: inhibition of ADP-induced platelet aggregation, increase in the frequency of isolated atria contractions and local increase in vascular permeability. All these activities were concentration dependent. Six micrograms of the peptides were still effective in increasing vascular permeability; in the in vitro systems the smallest effective dose ranged between 165 and 650 μg/ml.Following elution through a Sephadex G-25 gel with bidistilled water, four fractions were obtained. The second fraction (M.W. about 5,000) was the most active, followed by the first and then the third one; the fourth fraction was inactive.These data suggest that local accumulation of peptides in vivo may be of clinical relevancy.